Signals and Systems - Guo, Baolong; Zhu, Juanjuan (Information and Computer Engineering, 2018)
A compact overview on signals and systems, with emphasis on analysis of continuous and discrete systems in time domain. Frequency-domain analysis, transform analysis and state-space analysis are also discussed in detail. With abundant examples and exercises to facilitate learning, it is an ideal texts for graduate students and lecturers in signal processing, and communication engineering.